Quelles postures professionnelles de neutralité en éducation morale et civique (emc) en France ? - Gaïd Andro (Cahiers de la Recherche sur l'Education et les Savoirs)
This article is based on some reports written by the french National Education, but also on the research carried out among teachers on the professional difficulties experienced in teaching emc (moral and civic education) in classes. Our hypothesis is that, beyond the issue of pedagogical implementation, this teaching stumbles on two major professional difficulties that can be approach together: the inability to identify the learning that is really targeted (particularly in terms of scientific knowledge) and the difficulty of a finding a professional posture of “neutrality” that would permit the transmission of the republican values while dealing with the political, cultural and religious diversity in the class. Based on the observation of a group of beginning teachers in training, this article seeks to make visible what hinders the teachers in their representation of the expected professional posture and in the didactic distinction between opinions, knowledge and values within the classroom.